Reasons why women participate in physical activities - Mora, Blanca Sojo (2023)
With the purpose of determining the reasons why women do physical activities, a qualitative investigation was made in which the interview was used in depth with fourteen women who assist at the gym. As a main result, it was found that there are five reasons for doing physical activities. According to the repetition of the answer, the two main reasons are to stay healthy and to maintain a physical appearance. The research also showed that these two reasons vary according to age and time available to go to the gym. In addition, to answer the research question, what are the reasons why women engage in physical activity? This allowed us to find important data about the time devoted to exercise and some gender stereotypes related to physical activity.